L`entraînement combiné de la force et de l`endurance chez de jeunes footballeurs - Khanfir, M. A.; Kamoun, A.; Heubert, R.; Masmoudi, L. (Science & Sports, 2014)
Purpose: The purpose of the study was to examine the effects of a specific football concurrent strength and endurance training on maximal oxygen uptake (VO2max), running economy, running speed, maximal strength and vertical jump in young football players. Materials and methods: Ten young players attended a concurrent strength and endurance training program for 8 weeks. Physical performance and physiological variables were recorded before and after training in order to determine the effects of the specific combined training. Results: Concurrent specific football strength and endurance training improved physical qualities of young footballers. We found a significant improvement in VO2max by 4.9%, an increase of maximum aerobic velocity by 7.3%, an improvement in running economy by 5.7%, an improvement in vertical jumps: 15.6% in squat-jump and 13% in counter-movement jump, an increase of the maximal force in half-squat 60% in leg-extension 40% and in leg-curl 49% as well as an improvement in 5 m and 30 m sprint performance by 5.5% and 2% respectively. Specific strength training combined to endurance training with ball allows for improvement of physical qualities. Conclusion: Knowing the importance of technical and tactical work in football, endurance training with ball associated to a specific football strength training avoiding interference can present a real alternative to standard training.